2008
DOI: 10.1017/s0022112007009731
|View full text |Cite
|
Sign up to set email alerts
|

Landslide tsunamis propagating along a plane beach

Abstract: A forced two-horizontal-dimension analytical model is developed to investigate the distinguishing physical features of landslide-induced tsunamis generated and propagating on a plane beach. The analytical solution is employed to study the wave field at small times after the landslide motion starts. At larger times, the occurrence of transient edge waves travelling along the shoreline is demonstrated, showing the differences with the transient waves propagating over a bottom of constant depth. Results are satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 11 publications
6
83
0
Order By: Relevance
“…Since HA waves are generated at different depths as the slide moves down the incline, energy is transmitted to them at several frequencies and modes. In this case, the trapped low-frequency HA component could be significant and longshore HA waves could be used to predict incoming edge waves propagating along a beach (Sammarco & Renzi 2008). This intriguing research hypothesis is being considered in ongoing work.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since HA waves are generated at different depths as the slide moves down the incline, energy is transmitted to them at several frequencies and modes. In this case, the trapped low-frequency HA component could be significant and longshore HA waves could be used to predict incoming edge waves propagating along a beach (Sammarco & Renzi 2008). This intriguing research hypothesis is being considered in ongoing work.…”
Section: Discussionmentioning
confidence: 95%
“…Water is in the region x > 0, the shoreline is at x = 0. The planebeach geometry has important practical applications in tsunami models (Mei et al 2005;Sammarco & Renzi 2008). It is also particularly interesting as it allows one to obtain an exact analytical solution in terms of integrals of Bessel functions.…”
Section: Analytical Solution On a Plane Beachmentioning
confidence: 99%
“…Such an initial condition was then to be implemented in tsunami propagation and inundation models. Later, Sammarco and Renzi (2008) demonstrated that no analytical proof of the validity of the hot-start approach could be given, suggesting that such simplified models be used only for quick runup assessment. Indeed, Liu et al (2003) were among the first to recognise the importance of including the time history of the seafloor deformation in landslide tsunami modelling.…”
Section: State Of the Art Of Landslide Tsunami Modellingmentioning
confidence: 99%
“…The numerical results of Lynett and Liu (2005) highlighted the need to develop an appropriate analytical two-horizontal-dimension (2HD) model to explain such dynamics. Following the suggestion of Lynett and Liu (2005), Sammarco and Renzi (2008), Renzi and Sammarco (2010) and Renzi and Sammarco (2012) developed fully 2HD analytical models of landslide tsunami generation and propagation along a plane beach and around a conical island, induced by a sliding solid block. By using the forced linear shallow water equation, Sammarco and Renzi (2008) derived the analytical form of both the offshore component and the transient edge waves travelling along the shoreline of a plane beach.…”
Section: State Of the Art Of Landslide Tsunami Modellingmentioning
confidence: 99%
See 1 more Smart Citation